Studies on Electrochemical Deposition and Characterization of Co3o4 Films - P.N. Shelke; Y.B. Khollam; K.R. Patil; S.D. Gunjal; S.R. Jadkar; M.G. Takwale; K.C. Mohite (Журнал нано- та електронної фізики)
The Co3O4 films are prepared using two steps method. Initially, the films are electrochemically deposited on stainless steel and copper substrates from the solution containing CoSO4 and H3BO3 at various molar concentrations (0.05, 0.09, 0.13, 0.17, 0.21, 0.25 and 0.28 M) of CoCl2 in deposition bath. These as-deposited films are transformed into Co3O4 phase by heating them at 350 °C / 2 hr. These as-heated films are characterized by using X-ray diffraction, X-ray photoelectron spectroscopy, UV-Visible spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. From the characterization studies, the as-heated films are found to be containing single cubic spinel Co3O4 phase with high purity. The variation in molar concentration of CoCl2 in electrochemical deposition bath showed the profound effect on optical properties of Co3O4 films. The better optical properties, (i) absorptance (α) = 0.945, emittance (ε) = 0.071 and (ii) absorptance (α) = 0.950, emittance (ε) = 0.070 are obtained for the Co3O4 films prepared on stainless steel and copper substrates respectively at 0.28 M concentration of CoCl2 as compared to the data reported in literature. The strength and adhesion of as-heated films on both the substrates are found to be good for the molar concentrations of CoCl2 < 0.28 M.